Tackling Pediatric Obesity: Overcoming Challenges and Implementing Effective Management Practices - Angelina, Zenia; Tahalele, Paul L; Samsudin, Kevin; Ludia, Grace Margaretha; Gumelar, Agustinus Bimo (Universitas Andalas, 2024)
Obesity is described as an excess of adipose tissue accumulating in a body. Obesity can occur at any age, including pediatrics. In addition to the related health problems, obesity in children can increase the risk of developing chronic diseases. This literature review was carried out using search engines PubMed, Elsevier and Google Scholar, limiting the last 5 years to articles from 2019 to 2024. The main intervention to overcome pediatric obesity is dietary intervention, but a combination with other interventions such as physical activity, behavioral adjustments, and parental support may be more effective. With early intervention, pediatric obesity can be managed well